The Relationship Between The Level Of Knowledge And The Act Of Acne Self-Medication In Adolescents PIK-R Universitas Dharmas Indonesia - Ita Dwiaini (Jurnal EduHealth, 2022)
A skin disease that is often found in adolescents PIK-R universitas Dharmas Indonesia is acne vulgaris or acne. In overcoming acne, adolescents do self-medication as an alternative treatment. Limited knowledge about drugs and their use can lead to treatment errors in self-medication, adolescents tend to only know the trademark of the drug without knowing the efficacious substance. This research is an Analytical Survey study using a cross-sectional design. The population of this study was 208 adolescents who joined PIK-R Undhari and the sample used 80 adolescents who met the inclusion and exclusion criteria taken using purposive sampling sample techniques and instruments used in the form of questionnaires. Data analysis using univariate analysis and bivariate analysis (Chi-Square Test). The results of the knowledge level research for the high category were 81.5% and for the low category was 18.5%. As well as for acne selfmedication measures right by 90.8% and inappropriate by 9.2%. The test results using chi square p value = 0.001 (p < 0.50) showed that there was a relationship between the level of knowledge and acne selfmedication measures.